Relationship Dynamics and Perpetration of Intimate Partner Violence Among Female Chinese College Students. Issue 23 (December 2021) - Du, Jingshuai; Stith, Sandra; Durtschi, Jared; Spencer, Chelsea
In China, most intimate partner violence (IPV) research focuses on male perpetration and female victimization, whereas studies on dating violence and female IPV perpetration are less common. Although research on female IPV perpetration in China has surfaced recently, there have been limited studies examining factors related to female perpetration in dating relationships in China. In the current research, we sought to examine how relationship factors, including anger management, communication problems, relationship conflict, and relationship distress, are linked with female physical and psychological IPV perpetration. We included 857 female college students in three regions in China from the International Dating Violence database. We found that Chinese women's anger management skills and communication problems were both significantly associated with physical and psychological IPV perpetration on both minor and severe levels. Furthermore, we found that relationship conflict was significantly associated with minor and severe physical abuse perpetration and severe psychological abuse perpetration. Anger management skills moderated the negative effects of relationship conflict on minor physical IPV perpetration as well as minor and severe psychological IPV perpetration. Anger management skills also moderated the negative effects of relationship distress on minor and severe physical IPV perpetration among Chinese women. Our findings suggest that it may be important to explore the role of college women's anger management skills, communication problems, and conflict resolution skills in their dating relationships, as well as to develop female-based intervention programs to increase Chinese college women's relationship skills to reduce their levels of IPV perpetration.